Plasticizer Di-(2-Ethylhexyl)Phthalate Induces Epithelial-to-Mesenchymal Transition and Renal Fibrosis In Vitro and In Vivo. (14th April 2018) - Wu, Cheng-Tien; Wang, Ching-Chia; Huang, Li-Chen; Liu, Shing-Hwa; Chiang, Chih-Kang
Abstract: Plasticizer di-(2-ethylhexyl)phthalate (DEHP) is known as an endocrine disruptor and a peroxisome proliferator. A currently epidemiological study has suggested that daily high DEHP intake from phthalate-tainted foods in children may be a risk factor for renal dysfunction. DEHP can leach from medical devices such as blood storage bags and the tubing. Long-term exposure to DEHP is associated with nephropathy and exacerbates chronic kidney diseases (CKDs) progression. However, the detailed effects and molecular mechanisms remain unclear. Here, we hypothesized that DEHP and its major metabolite mono-(2-ethylhexyl)phthalate (MEHP) incited epithelial-to-mesenchymal transition (EMT) and lead to aggravate renal fibrosis progression. Treatment with low-cytotoxic concentration DEHP, but not MEHP, for 72 h obviously induced the morphological and phenotypic changes and EMT markers induction in normal rat renal tubular epithelial cells (NRK-52E). AKT inhibitor MK-2206 inhibited DEHP-induced EMT features and signals of AKT phosphorylation and downstream NF-κB and GSK3β. DEHP did not affect the expression of transforming growth factor-β1 mRNA. DEHP down-regulated the peroxisome proliferator-activated receptor (PPAR)α and PPARγ protein expressions. PPARγ agonist pioglitazone partially and significantly inhibited DEHP-induced EMT induction. In vivo DEHP exposure for 6 weeks enhanced the renal dysfunction and renal fibrosis and mortality rate, but decreased the PPARα and PPARγ protein expressions, in a folic acid-induced kidney fibrosis mouse model. Taken together, these results demonstrate for the first time that DEHP arouses EMT induction and renal fibrosis progression in renal tubular cells and is associated with PPARs downregulation. DEHP exposure potentially exacerbated renal fibrosis/nephropathy in a kidney disease condition.